PENGARUH LAYANAN BIMBINGAN KLASIKAL MENGGUNAKAN MEDIA TIKTOK DAN BUKU SAKU UNTUK MENINGKATKAN PENGETAHUAN PERILAKU SEKS BERISIKO SISWA SMAN 3 PEKANBARU - Tiara Zahrani; Elni Yakub; Siska Mardes (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This research aims to find out whether classical guidance services using TikTok media and pocket books have an effect in increasing knowledge about risky sexual behavior in class XI students at SMA Negeri 3 Pekanbaru. This research is a quantitative experimental research in the form of a one group pretest-posttest design, with a one group subject design. Data collection was carried out by distributing pretest posttest instruments on knowledge of risky sexual behavior. The data that has been collected is then analyzed using the paired sample T test and the product moment correlation test with the help of the SPSS Version 25 for Windows program. Based on the results of data analysis obtained, it was found that there was an increase in students' knowledge of risky sexual behavior before and after being given treatment in the form of classical guidance services using TikTok media and pocket books. The results of the paired sample T test also showed that there were differences in students' level of knowledge of risky sexual behavior before and after being given classical guidance services using TikTok media and pocket books. The influence of classical guidance services using TikTok media and pocket books on increasing students' risky sexual behavior is 44% and the remaining 56% is influenced by external factors such as age, social media, friends, family. The magnitude of the influence of classical guidance services using TikTok media and pocket books on increasing knowledge of risky sexual behavior is in the medium category.